2017
DOI: 10.1038/npp.2017.183
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter and Reward Anticipation in a Dimensional Perspective: A Multimodal Brain Imaging Study

Abstract: Dopamine function and reward processing are highly interrelated and involve common brain regions afferent to the nucleus accumbens, within the mesolimbic pathway. Although dopamine function and reward system neural activity are impaired in most psychiatric disorders, it is unknown whether alterations in the dopamine system underlie variations in reward processing across a continuum encompassing health and these disorders. We explored the relationship between dopamine function and neural activity during reward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…More specifically, studies in rodents that used optogenetic stimulation of dopaminergic VTA neurons have shown both increased striatal activity (Ferenczi et al, 2015;Lohani et al, 2017) and no effect on striatal activity (Brocka et al, 2018) and therefore it remains unknown whether dopaminergic activity plays a causal role in striatal activity. In support of a link between DA functioning and striatal neurovascular response, human studies found a correlation between reward-induced striatal activity as measured with fMRI and reward-induced DA release (Schott et al, 2008) or dopamine transporter availability (Dubol et al, 2018) as measured with PET. In conclusion, these results suggests that DA functioning plays a role in striatal responses to rewards and that alterations in the DA system in siblings may underlie altered reward responses following stress.…”
Section: Reward Feedback Response In Siblings Of Schizophrenia Patientsmentioning
confidence: 87%
“…More specifically, studies in rodents that used optogenetic stimulation of dopaminergic VTA neurons have shown both increased striatal activity (Ferenczi et al, 2015;Lohani et al, 2017) and no effect on striatal activity (Brocka et al, 2018) and therefore it remains unknown whether dopaminergic activity plays a causal role in striatal activity. In support of a link between DA functioning and striatal neurovascular response, human studies found a correlation between reward-induced striatal activity as measured with fMRI and reward-induced DA release (Schott et al, 2008) or dopamine transporter availability (Dubol et al, 2018) as measured with PET. In conclusion, these results suggests that DA functioning plays a role in striatal responses to rewards and that alterations in the DA system in siblings may underlie altered reward responses following stress.…”
Section: Reward Feedback Response In Siblings Of Schizophrenia Patientsmentioning
confidence: 87%
“…Together with subsequent dysfunction in dopaminergic and glutamatergic signaling, increased inflammation may lead to motivational deficits and negative symptoms in patient with schizophrenia. schizophrenia and major depression has been the positive relationship between dopamine transporter availability and the fMRI BOLD response in the nucleus accumbens to reward anticipation has been described in both disorders (123). Individuals at clinical high-risk for schizophrenia from the North American Prodrome Longitudinal Study (NAPLS) cohort have depressive symptoms that have been shown to be associated with negative symptoms (124).…”
Section: The Role Of Inflammation In Reward Processing Deficits In Psmentioning
confidence: 99%
“…The DA system in the NAc is also involved in emotion-related behaviors, particularly behaviors related to depression (Luscher and Malenka, 2011 ; Lammel et al, 2014 ; Li et al, 2019 ). Dopaminergic dysfunction is a common mechanism in a variety of reward and motivational disorders, including addiction and depression (Dubol et al, 2018 ).…”
Section: Possible Influencing Factors That Mediate the Comorbidity Ofmentioning
confidence: 99%